TREM2 Mediates Microglial Anti-Inflammatory Activations in Alzheimer’s Disease: Lessons Learned from Transcriptomics - Feng Xue (Cells, 2021)
Alzheimer’s disease (AD) is a lethal neurodegenerative disorder primarily affecting the aged population. The etiopathogenesis of AD, especially that of the sporadic type, remains elusive. The triggering receptor expressed on myeloid cells 2 (TREM2), a member of TREM immunoglobulin superfamily, plays a critical role in microglial physiology. Missense mutations in human TREM2 are determined as genetic risk factors associated with the development of sporadic AD. However, the roles of TREM2 in the pathogenesis of AD are still to be established. In this review, we outlined the influence of Trem2 on balance of pro- and anti-inflammatory microglial activations from a perspective of AD mouse model transcriptomics. On this basis, we further speculated the roles of TREM2 in different stages of AD, which may shed light to the development of TREM2-targeted strategy for the prevention and treatment of this neurodegenerative disorder.